Effect of autologous hematopoietic stem cell transplantation for patients with peripheral T-cell lymphoma in China: A propensity score-matched analysis - Gao, Hongye; Wu, Meng; Hu, Shaoxuan; Ding, Ning; Ji, Xinqiang; Mi, Lan; Wang, Xiaopei; Song, Yuqin; Zhu, Jun; Liu, Weiping (Frontiers in Oncology, 2022)
Background: The role of consolidation therapy with autologous stem cell transplantation (ASCT) in patients with peripheral T-cell lymphoma (PTCL) in first complete remission (CR1) or partial remission (PR1) remains controversial. The existing data from China are limited. Therefore, we aimed to investigate the effect of ASCT on the survival of Chinese patients with PTCL showing response to induction chemotherapy at our hospital. Methods: We retrospectively reviewed the data of patients with PTCL (excluding Natural killer/T cell lymphoma) in CR1 or PR1 treated at Peking University Hospital &Institute from 1996 to 2020. Propensity score matching (PSM) was used to balance clinical characteristics between the ASCT and non-ASCT groups. The primary endpoints were event-free survival (EFS) and overall survival (OS). Results: Of the 414 selected patients, 73 received ASCT consolidation and 341 did not. Over a median follow-up of 5.7 years, survival was significantly better in the ASCT group than in the non-ASCT group (median EFS, 8.1 years vs. 2.8 years, P = 0.002; median OS, 14.9 years vs. 10.2 years, P = 0.007). The 5-year EFS and OS rates were 68.4% and 77.0% in ASCT group, and 43.2% and 57.6% in non-ASCT group, respectively. The survival benefit was confirmed in the propensity score matched cohort (46 patients who received ASCT and 84 patients who did not receive ASCT): P = 0.007 for median EFS and P = 0.022 for the median OS. Cox regression analysis showed that ASCT was independently associated with better survival: hazard ratio (HR) for EFS, 0.46 (95% CI: 0.28-0.76); HR for OS, 0.50 (95% CI: 0.31-0.84). Subgroup analysis showed that ASCT was more likely to benefit higher-risk patients and those with advanced disease. Among the subtypes of PTCL, the benefit was significant in angioimmunoblastic T-cell lymphoma (HR = 0.26 [95% CI: 0.10-0.66] for EFS and 0.29 [95% CI: 0.12-0.74] for OS), but not in the other subtypes. Conclusion: ASCT may improve the long-term survival of patients with PTCL in first CR or PR, especially for patients with angioimmunoblastic T-cell lymphoma. The specific groups most likely to benefit from upfront ASCT need to be clearly identified.